If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+2x+(-4+9)=8x+-10
We move all terms to the left:
5x+2x+(-4+9)-(8x+-10)=0
We add all the numbers together, and all the variables
5x+2x-(8x-10)+5=0
We add all the numbers together, and all the variables
7x-(8x-10)+5=0
We get rid of parentheses
7x-8x+10+5=0
We add all the numbers together, and all the variables
-1x+15=0
We move all terms containing x to the left, all other terms to the right
-x=-15
x=-15/-1
x=+15
| x^2=273.59 | | -10x+2x+(-4+9)=-8x+5 | | a-20=32 | | x=2/3x-7 | | -7(4x+6)=-(5x+1) | | d+36=58 | | 2x+12+19=x+16 | | 25-a=2 | | 2.5x+30=150 | | t-23=24 | | w-8=15 | | 2y-4=13 | | 4^1-2x=0.0625 | | 22x=66x= | | 100=t+25 | | 114=3(y+1 | | 2π(9)+2π(3)(8)=s | | 2(3.14)(9)+2(3.14)(3)(7)=s | | 5+20m−2m=-13 | | t+15=99 | | 56+68+x+66=180 | | 3x +1=11 | | x^2=9*15 | | 3.6/x=10.8/12 | | 15q=60,q= | | 3x-11=-5 | | 12x−1=11 | | 5^7•5n=5^10 | | 9x-7=-9+15 | | -x2-5x+1=22 | | 0.5=0.2+x-0.2x | | 6b+4b+40=180 |